The concentration of histamine in plasma and tissues of the primary ductal breast cancers - von Mach-Szczypiński, Jaroslaw; Sieja, Krzysztof; Stanosz, Małgorzata; Olewniczak, Sławomir (Contemporary Oncology/Współczesna Onkologia, 2003)
The aims of the study were: 1) to estimate histamine concentration in serum in women suffering from breast cancer and healthy ones, 2) to evaluate histamine concentration in neoplasmatic and perineoplasmatic tissues of breast cancers and normal tissues of healthy women, 3) to assess enzymes connected with histamine metabolism (histidine decarboxylase, histamine diaminoxydase) in cancerous and pericancerous tissues in comparison to normal tissues of the control group, 4) to evaluate the relationships between the concentration of histamine in cancerous and pericancerous tissues, and the activities of the enzymes which are involued in the histamine metabolism. Material and methods. The study comprised 155 women aged from 38 to 70 divided into two groups: control and study. The first (control) group comprised 60 women (mean age 50.6±6.3) in whom mammoplasties were performed. The second (study) group consisted of 95 women (mean age 51.9±1.7) with mainly invasive ductal breast cancers. In both groups the concentration of histamine in serum was studied. Tissues (cancerous and pericancerous) were taken from women of the control and study groups for biochemical assays of histamine and its enzymes. Conclusions: 1) significant increase of the concentration of histamine in cancerous tissues of ductal breast cancer is caused by the increased synthesis and decreased inactivation of histamine, 2) the causes of disturbed histamine metabolism in cancerous tissues of ductal breast cancers include significantly increased histidine decarboxylase and decreased histamine diaminoxydase activity, 3) higher concentration of histamine in serum of women with breast cancer than in healthy ones suggests that newly synthesized histamine is being released from from the breast cancer tissue into the serum.